Edukasi Kepatuhan Minum Obat Pada Ny. W Dengan Hipertensi (Sebuah Laporan Kasus Pendekatan Kedokteran Keluarga) - Yusuf Alam Romadhon; Marti Eka Ning Tias; Lili Puspadewi; Nurnawati Soga (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
A 70 years old woman was diagnosed with hypertension for 2 years. Diagnosis of hypertension is known from the elderly posyandu examination. There is a family history of hypertension, diabetes, goitre nodusa, and COPD. Two extended family members have risky behaviors, namely smoking and alcohol. The patient lives in the same house with a smoking family member. The type of extended family and entering stage five according to Duval. The relationship between family members is harmonious, APGAR Family shows a healthy function. The SCREEM function stands out, the patient has a Javanese ethnic background, is “sensitive” to what neighbors say, does not optimize the JKS-KIN card they have, and has low formal education. Biomedical diagnosis: hypertension stage I (155/90 mmHg), obesity grade I (BMI 24.9 kg / M2). Holistic diagnosis: psycho-emotionally there is a thought that the disease is getting worse, so she often feel worried about it. The caring behavior of family members is good, but knowledge of the disease and efforts to manage it are still lacking, so that they do not take medication regularly, and the diet is not balanced. The interventions given were pharmacological therapy from the Puskesmas, and from the author's team, providing education on the importance of regularly taking medication, and making a balanced diet program. Blood pressure fell at the following two visits, 135/90 mmHg and 135/85 mmHg, respectively.